Potential of electrokinetic response for the analysis of solid-liquid mixture during mechanical expression - Iwata, Masashi; Shimoizu, Kazuya; Iwasaki, Tomohiro; Jami, Mohammed Saedi (2019)
Expression is the separation of liquid from a solid/liquid system by compression due to the movement of the retaining walls of the filter chamber. In the expression of slurry material, the application of mechanical pressure to the retaining walls causes a sudden increase of hydraulic pressure uniformly throughout the slurry. Initially, the process of expression proceeds based on the principle of filtration, where the thickness of filter cake increases over time. Filtration terminates when the whole slurry forms a layer of filter cake, and the consolidation of the cake follows. Exact identification of the time when the chamber is filled with the cake is essential for an effective expression operation. The electrokinetic response of expressed material provides us with some information on the status of the filter chamber. In this work, we have measured the time course of electric potential difference (EPD) between the retaining walls to elucidate the electrokinetic aspects of mechanical dewatering. The experimental apparatus used in this study consists essentially of a piston press with a cylinder and a piston. Filter media are placed at the cylinder bottom and the very end of the piston. EPD between the filter media was monitored during the experiment. As can be seen from the figure, the absolute value of EPD increases with the progress of the filtration period, followed by the decrease during the consolidation period. It was observed that the time when the absolute value of EPD began to decline coincides with the time when the filtration period ended. We have derived a theoretical equation of streaming potential for a flow path of the expressed material and combined it with filtration and consolidation theories to calculate the theoretical time course of EPD of expressed material. It has been found that EPD reflects liquid pressure variation throughout the solid/liquid mixture.